2022
DOI: 10.46606/eajess2022v03i01.0142
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Tanzania Higher Learning Institutions to e- Learning during Covid-19 Pandemic

Abstract: This study examined how the Tanzanian Higher Learning Institutions (HLIs) responded to the e-learning implementation during the COVID-19 pandemic period. It employed the Actor Network Theory that informs the socio-technical interactions. The study employed an explorative case study design with qualitative techniques, involving a total of 13 participants from selected HLIs. A thematic analysis framework was used to analyze data. The study revealed that HLIs in Tanzania have partially implemented e-learning syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…The majority of Malaysia's 20 public institutions were found to have responded by promoting or mandating online learning, whether using in-house e-learning platforms, live broadcasting on Facebook or YouTube, Lightboard Video Technology, or Zoom [19]. In Tanzania, Moodle and other LMSs were primarily developed and implemented [20].…”
Section: The Use Of Lms During Covid-19mentioning
confidence: 99%
“…The majority of Malaysia's 20 public institutions were found to have responded by promoting or mandating online learning, whether using in-house e-learning platforms, live broadcasting on Facebook or YouTube, Lightboard Video Technology, or Zoom [19]. In Tanzania, Moodle and other LMSs were primarily developed and implemented [20].…”
Section: The Use Of Lms During Covid-19mentioning
confidence: 99%
“…HEIs in Tanzania have been reported to face a number of challenges, such as limited internet access, unavailability of relevant digital content, and outdated ICT infrastructures, just to mention a few. Several studies in Tanzania in HEIs report that there is shallow adoption of technological solutions, something that limits the development of digital literacy skills among students [43,49,50]. For instance, in the survey that involved 126 countries, including Tanzania, around 17% were reported to have been using LMS regularly while only 11% were using it very often, and the remaining 72% were not using distance learning [27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate several barriers to the successful integration of technology for developing digital literacy skills among learners in HLIs in developing countries, notably Tanzania [7,33,46,49,51]. Other studies have found that the main obstacles to the use of LMS in HEIs in Tanzania include a lack of access to computers and the Internet, limited Internet speed, a lack of policies, and expertise in creating digital resources [44,45,47].…”
Section: Introductionmentioning
confidence: 99%
“…This will affect the usage and development of online/blended learning environments, and increase the gap between the students in online learning experiences in higher learning institutions in the country, which is then affecting their behavior intention in the adoption and use of technology. Besides, it also affects the requirement to articulate harnessing ICT opportunities to meet the Vision 2025 goals that emphasized the determination of applications of distance education, e-learning, m-learning, and blended learning (Ministry of Education, 2016;Mwakyusa & Ng`webeya, 2022). this study is guided by the Activity Theory (AT).…”
Section: Introductionmentioning
confidence: 99%